The effects of Se/S ratio on the photoelectric properties of nitrogen -doped graphene quantum dots decorated CdSxSe1-x composites. Issue 4 (15th February 2022) - Lei, Yun; Du, Beibei; Du, Peng; Wu, Yuncui; Wang, Yongqin; Li, Can; Luo, Linhui; Zou, Bingsuo
Abstract: In the work, CdSx Se1-x /N-GQDs composites were fabricated via a simple one-step hydrothermal process and their tunable composition, structure and photoelectric properties were characterized by various techniques. The photoelectric properties of CdSx Se1-x /N-GQDs could be adjusted by different Se/S ratios and tunable band-gaps. CdSx Se1-x /N-GQDs composites reached the optimal photocurrent response and the lowest interfacial impedance at the Se/S ratio of 0.75:0.25. Mott-Schottky plots and LSV spectra showed that the n-type CdS0.25 Se0.75 /N-GQDs presented a higher carrier density under light illumination. The excellent properties of the composites could be attributed to the mechanism involved in the excitation and electron-transfer process. On one hand, the band-gap of CdS0.25 Se0.75 /N-GQDs was narrowed, and more electrons were excited by the lower band-gap energy to promote a superior electron separation and transportation. On the other hand, N-GQDs acted as charge carriers and conductive way providers for electron-transfer instead of electron-hole recombination in the composites.